Molecular cytogenetic analyses reveal extensive chromosomal rearrangements and novel B chromosomes in Moenkhausia (Teleostei, characidae) - Do Nascimento, Cristiano Neves [UNESP] (2020)
The cytogenetic characteristics of five fish species of the Moenkhausia are described, based on the analysis of specimens collected in different headwater. All the species analyzed presented 2n=50 chromosomes. The C-banding revealed a similar distribution pattern of heterochromatic blocks in all the species, except Moenkhausia nigromarginata. The 5S rDNA sites were distributed on multiple chromosome pairs in all five species. Single and multiple histone H1 sites were observed in all the species, and histone H1 was shown to be co-located with the 18S rRNA gene in a single chromosome pair. The U2 snDNA gene was distributed at multiple sites in all the Moenkhausia species. The presence of B microchromosomes was confirmed in Moenkhausia forestii, while individuals of the three study populations of Moenkhausia oligolepis presented three morphologically distinct types of B chromosome. The chromosomal mapping of the 18S rDNA sites using the FISH technique revealed signals in the B chromosomes ofM. forestii, while clusters of the H1 histone and U2 snDNA genes were found in the B chromosomes of M. forestii and M. oligolepis. The classical and molecular cytogenetic markers used in this study revealed ample variation in the Moenkhausia karyotypes, reflecting the dynamic nature of the chromosomal evolution.